Case Report: Successful immune checkpoint inhibitor-based rechallenge in a patient with advanced renal clear cell cancer - He, Shengxiu; Wang, Liang; Sun, Yan; Du, Huakun; Yu, Xiaomin (Frontiers in Immunology, 2023)
With the rapidly evolving of immune checkpoint inhibitors (ICIs), it has shown remarkable clinical benefits in treating various cancers. However, immune-related adverse events (irAEs) remain a significant challenge in the management of patients undergoing immunotherapy. There are limited data about immunotherapy re-challenge in patients with renal clear cell cancer who had irAE in the initial ICI therapy. In this study, we reported the case of a patient with advanced renal clear cell cancer who developed serious irAEs but also achieved a partial remission of tumor after ICI combined with pazopanib in the first-line treatment. After intravenous methylprednisolone therapy for two weeks, the patient fully recovered from treatment-related toxicities. After a multidisciplinary treatment (MDT) discussion and a communication with the patient, the decision was made to undergo a new fully humanized programmed death 1 (PD-1) agent, zimberelimab, combined with pazopanib for immune restart therapy. After two cycles of treatment, the patient demonstrated a partial response (PR), and the disease remained in continuous remission without any irAE at our last follow-up after 14 months’ treatment. Re-challenging with immunotherapy after irAEs is an emerging strategy that offers the potential for additional clinical benefits to previously responding patients. However, careful patient selection and monitoring are essential to maximize the safety and efficacy of this approach.